Choice vs. voice? PPI policies and the re-positioning of the state in England and Wales - David Hughes (Health Expectations, 2009)
Changing patient and public involvement (PPI) policies in England and Wales are analysed against the background of wider National Health Service (NHS) reforms and regulatory frameworks. We argue that the growing divergence of health policies is accompanied by a re-positioning of the state vis-à-vis PPI, characterized by different mixes of centralized and decentralized regulatory instruments. In England, continued hierarchical control is combined with the delegation of responsibilities for the oversight and organization of PPI to external institutions such as the Care Quality Commission and local involvement networks, in support of the government’s policy agenda of increasing marketization. In Wales, which has rejected market reforms and economic regulation, decentralization is occurring through the use of mixed regulatory approaches and networks suited to the small-country governance model, and seeks to benefit from the close proximity of central and local actors by creating new forms of engagement while maintaining central steering of service planning. Whereas English PPI policies have emerged in tandem with a pluralistic supply-side market and combine new institutional arrangements for patient ‘choice’ with other forms of involvement, the Welsh policies focus on ‘voice’ within a largely publicly-delivered service.The English reforms draw on theories of economic regulation and the experience of independent regulation in the utilities sector, while the Welsh model of local service integration has been more influenced by reforms in local government. Such transfers of governance instruments from other public service sectors to the NHS may be problematic.